Bacteriological and Pathological Investigation of Nasal Passage Infections of Chickens (Gallus gallus) (The Agriculturists, 2013)
An experiment was conducted at the Bangladesh Agricultural University, Mymensingh during July 2011 to May 2012 to investigate the prevalence of bacteria as well as pathological lesions in the nasal passages of dead chickens. Thirty nasal passage swabs from 30 dead birds (20 from SK Veterinary Diagnostic Centre (SKVDC) and 10 from the Department of Pathology, BAU were collected in sterile nutrient broth. The histopathological samples (n=6) were collected in 10% neutral buffered formalin. The isolation and identification of bacteria were performed by culturing in different media, staining and biochemical tests. The collected tissues were fixed, processed, sectioned, stained and studied with light microscope. The prevalence of bacteria 30.43% Escherichia coli, 47.83% Staphylococcus sp., 13.04% Pasteurella sp., and 8.69% Klebsiella sp. were found in nasal passages (n=30) of dead chickens. Two cases of mixed infection with E. coli and Pasteurella isolates, and one case with Klebsiella and E. coli isolates were identified. Six tissue samples of grossly identifiable lesions such as congested and mucus filled nasal passages from 6 dead chickens were processed for histopathology. Microscopically, the section of nasal passages in general showed congested mucosa with excessive infiltration of heterophils and lymphocytes. The lining epithelia of nasal passage revealed acanthosis, hyperkeratosis and disruption of nasal epithelia. There was also hyperplasia of different mucous glands of nasal passages. Klebsiella sp. affected nasal tissues showed comparatively severe lesions than that of other bacterial infection in chickens. DOI: http://dx.doi.org/10.3329/agric.v11i1.15241 The Agriculturists 2013; 11(1) 47-55